Carer involvement in compulsory out-patient psychiatric care in England - Jorun Rugkåsa; Krysia Canvin (BMC, 2017)
Abstract Background There is an expectation in current heath care policy that family carers are involved in service delivery. This is also the case with compulsory outpatient mental health care, Community Treatment Orders (CTOs) that were introduced in England in 2008. No study has systematically investigated family involvement through the CTO process. Method We conducted qualitative interviews with 24 family carers to ascertain their views and experiences of involvement in CTOs. The transcripts were subjected to thematic analysis that incorporated both deductive and inductive elements. Results We found significant variation in both the type and extent of family carer involvement throughout the CTO process (initiation, recall to hospital, renewal, tribunal hearings, discharge). Some were satisfied with their level of involvement while others felt (at least partly) excluded or that they wanted to be more involved. Some wanted less involvement than what they had. From the interviews we identified key factors shaping carers' involvement. These included: perceptions of patient preference; concern over the relationship to the patient; carers' knowledge of the CTO and of the potential for carer involvement; access to and relationships with health professionals; issues of patient confidentiality; opportunities for private discussions, and; health professionals limiting involvement. These factors show that health professionals have many opportunities to facilitate, or hinder, carer involvement. The various roles attributed to carers, such 'proxy' for patient decision, 'gatekeeper' to services, 'mother' or 'expert carer', however, conflict with one another and make the overall role unclear. Conclusions There is a need for clarification of the expectations of carers in individual care situations, for carers to be equipped with the information they need to in order to be involved, and for services to find flexible and innovative ways of ensuring continuous, open communication. The introduction of CTOs in England has not been successful in its ambition for carer involvement.